Experimental and Numerical Simulation Study on the Shock and Vibration Effect of OD1422-X80 Mainline Natural Gas Pipeline Explosion - Huayuan Ma; Mingshou Zhong; Xinghua Li; Quanmin Xie; You Zhou; Qin Yin (Shock and Vibration)
In this paper, the explosion experiment of the OD1422-X80 natural gas pipeline was carried out. The phenomenon of pipeline explosion was recorded, and a large amount of data on vibration effects were obtained. The data showed that the ground vibration during the explosion was mainly caused by the physical explosion process, and the subsequent gas explosion did not produce strong vibration. Based on the ANSYS/LS-DYNA platform, a numerical calculation model of this experiment was established. The numerical results agreed well with the experimental results. Simulation and experimental results showed that when the gas pressure in the pipe was lower than 7 MPa, the pipeline cracks stop growing. The maximum speed of the pipe wall moving outward reached 50 m/s, which formed a huge impact compression effect on the surrounding soil. This state spread to distant places and gradually decayed into an elastic stress wave, which formed a ground vibration effect. Time-frequency analysis was introduced into the vibration signal processing. The analysis results showed that the main frequency of pipeline explosion vibration was distributed around 10 Hz and had a long duration. The research results provided a reference for subsequent gas pipeline explosion test and numerical simulation research.